IL‐33 promotes MHC class II expression in murine mast cells. Issue 3 (6th May 2015) - Ito, Tomonobu; Egusa, Chizu; Maeda, Tatsuo; Numata, Takafumi; Nakano, Nobuhiro; Nishiyama, Chiharu; Tsuboi, Ryoji
Abstract Mast cells (MCs), recognized as tissue‐resident cells of hematopoietic origin, are involved in cellular and pathological manifestations of allergic disorders including atopic dermatitis. IL‐33, a member of the IL‐1 cytokine family, activates Th2‐type immune responses, and promotes the degranulation and maturation of MCs. However, it is uncertain whether IL‐33 treatment induces mature mast cells to acquire the characteristics of the monocyte‐dendritic cell lineage.We investigated the effect of IL‐33 on the MHC class II expression and function of murine mast cells. IL‐33‐treated mature murine bone marrow‐derived mast cells (BMMCs) were analyzed by FACS, real‐time PCR, chromatin immunoprecipitation (ChIP) assay, and Western blotting. The morphology and degranulation activity of BMMCs and T‐cell activation by BMMCs were also examined. BMMCs treated with IL‐33 for 10 days induced cell surface expression of the MHC class II protein, whereas the expression of FcεRI and c‐kit was not affected by IL‐33. The expression of CIITA, driven from pIII and pIV, was up‐regulated in IL‐33‐treated BMMCs. The amount of PU.1 mRNA and protein significantly increased in IL‐33‐treated BMMCs. The ChIP assay showed PU.1 binding to CIITA pIII, and enhanced histone acetylation due to IL‐33 treatment. Syngeneic T cells were activated by co‐culture with IL‐33‐treated BMMCs, although the expression of the co‐stimulatory molecules, CD40, CD80, CD86, and PDL‐1, was not detected. Mast cells express MHC class II after prolonged exposure to IL‐33, probably due to enhanced recruitment of PU.1 to CIITA pIII, resulting in transactivation of CIITA and MHC class II. IL‐33 is an important cytokine in allergic disorders. Mast cells have the ability to express MHC class II after prolonged exposure to IL‐33 in a murine model. IL‐33 holds a key to understanding the etiology of atopic dermatitis.